Chinese traditional theatre and male dan : social power, cultural change and gender relations - Guo, Chao (Abindon, Oxon ; New York : Routledge, 2022)
"This book examines male dan, a male actor who performs female roles in Chinese theatre. Through the rise, fall and tenuous survival of male dan in Chinese history, Guo Chao reflects the transformations in the social zeitgeist in China, especially the politics of gender and sexuality. The breadth of this study reflects a diversified set of sources, ranging from classical to contemporary texts (texts of jingju plays, memoirs, collections of notation books) and other commentaries and critical evaluations of dan actors (in both English and Chinese languages), to video and audio materials, films, and personal interviews. This book will be of great interest to students and scholars of East Asian/Chinese studies across the fields of theatre, history, culture, and literature"--
List of FiguresAbbreviations and AcronymsPrefaceAcknowledgementsNote to the Reader1 Introduction: Chinese Traditional Theatre and Male Dan2 Imaginary Romance: The Rise of Male Dan and Their Connections to the Scholar-Elite in the Ming Dynasty3 Commodified Intimacy: Male Dan, Boy Courtesans and Well-off Patrons in the Qing Dynasty4 At the Dawn of a Modern Nation: Three Keys in Male Dan5 Between Scholar-Intellectuals and Theatrical Aficionados: Male Dan under Siege6 Reinventing Disciplinary Femininity: Technical Innovations of Male Dan 7 Reconstructing Femininity through Masculinity: The Prohibition of Male Dan in Socialist China8 The Mythopoeia of Homosexuality: Aesthetic Representations of Male Dan in Contemporary Culture9 A Millennial Predicament: Male Dan in a Homophobic Country10 Coda: Male Dan and Chinese Society in TransitionAppendix A: Biographical Notes on Key Historical FiguresAppendix B: Synopses of Major Plays Mentioned in the TextGlossary Index
Keywords: Theater -- China -- History; Sex role in the theater; Chinese drama -- History and criticism; HISTORY / Asia / China; PERFORMING ARTS / General; SOCIAL SCIENCE / Anthropology / Cultural